THE APPROPRIATION OF SIN SAIMDANG AS A SYMBOL OF MODERNIZATION DURING THE PARK CHUNG HEE ERA - SÎNTIONEAN, Codruţa (Studia Universitatis Babeș-Bolyai Philologia, 2020)
The Appropriation of Sin Saimdang as a Symbol of Modernization during the Park Chung Hee Era. In the aftermath of her death, Sin Saimdang (1504-1551), mother of Neo-Confucian philosopher Yulgok Yi I, was gradually transformed into a symbol of motherhood and female domesticity, an image which, in time, overshadowed her accomplishments as a painter. Little personal details are known about her, other than the brief characterization made posthumously by Yulgok. Everything else in her biography is anecdotal and was added by Yulgok’s followers, even centuries after her death. All these layers of interpretation have made Saimdang an abstract symbol, not a real historical person. The present study investigates how this symbol was instrumented by the Park Chung Hee government (1961-1979) in order to mobilize housewives to participate in the developmentalist projects of the state. The paper argues that Sin Saimdang has been promoted by the state, with the contribution of women’s organizations, as a symbol of modernization, used in gendered national mobilization. Various commemoration practices–a memorial day and a national prize honoring Saimdang, statues erected in the 1970s, the restoration of her ancestral home–stand as evidence of the coordinated efforts made by the state and women’s associations to disseminate Sin Saimdang as a model for the modern Korean woman. REZUMAT. Transformarea lui Sin Saimdang într-un simbol al modernizării sub regimul lui Park Chung Hee. După moartea sa, Sin Saimdang (1504-1551), mama filosofului neo-confucianist Yulgok Yi I, a fost transformată treptat într-un simbol al maternității și al feminității domestice, o imagine care, în timp, i-a umbrit realizările din domeniul artei picturale. Puține detalii personale sunt cunoscute despre ea, cu excepția scurtei caracterizări realizate postum de Yulgok. Toate celelalte amănunte din biografia ei sunt elemente anecdotice, adăugate de discipolii lui Yulgok, chiar la secole distanță după moartea lui Saimdang. Toate aceste paliere de interpretare au făcut din ea un simbol abstract, nu o persoană reală. Studiul de față investighează modul cum acest simbol a fost utilizat de guvernul dictatorului Park Chung Hee (1961-1979) pentru a mobiliza gospodinele casnice să participle la proiectele de dezvoltare ale statului. Lucrarea argumentează că Sin Saimdang a fost promovată de către stat, cu ajutorul organizațiilor de femei, drept simbol al modernizării, folosit pentru mobilizarea națională diferențiată pe genuri. Diverse practici de comemorare – o zi memorială și un premiu național onorând numele lui Saimdang, statui ridicate în deceniul 1970, restaurarea casei sale părintești – reprezintă o dovadă a eforturilor concertate ale statului și organizațiilor de femei să o promoveze pe Sin Saimdang ca model al femeii coreene moderne. Cuvinte-cheie: Park Chung Hee, Sin Saimdang, Yulgok Yi I, practici de comemorare, modernizare, gen.